(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2020)
The research aimed to estimate the amount of liquidity surplus in the private banking sector in the Syrian Arab Republic during the period between 2007-2018 and find out its impact on economic growth by studying its impact on the gross domestic product. Monthly GDP data and financial reports issued by operating private banks in the Syrian Arab Republic were used. The study pointed to declining contribution of the financial and insurance sector to the gross domestic product compared to previous years. Researchers had used EViews 10+ package to determine the optimal lag periods for the series which was 4 lags. Vector Auto regression (VAR) test had confirmed an existence of direct relationship between liquidity surplus and GDP. On long term, According to Impulse response function test, the gross domestic product is expected to move in an upward direction after declining during the first 14 periods as a result of directing the liquidity surplus of the private banking sector in the Syrian Arab Republic to support investment and financing sector.